Developmental influences on symptom expression in antipsychotic-naïve first-episode psychosis. Issue 9 (6th July 2022) - Bridgwater, Miranda; Bachman, Peter; Tervo-Clemmens, Brenden; Haas, Gretchen; Hayes, Rebecca; Luna, Beatriz; Salisbury, Dean F.; Jalbrzikowski, Maria
Abstract: Background: The neurodevelopmental model of psychosis was established over 30 years ago; however, the developmental influence on psychotic symptom expression – how age affects clinical presentation in first-episode psychosis – has not been thoroughly investigated. Methods: Using generalized additive modeling, which allows for linear and non-linear functional forms of age-related change, we leveraged symptom data from a large sample of antipsychotic-naïve individuals with first-episode psychosis ( N = 340, 12–40 years, 1–12 visits), collected at the University of Pittsburgh from 1990 to 2017. We examined relationships between age and severity of perceptual and non-perceptual positive symptoms and negative symptoms. We tested for age-associated effects on change in positive or negative symptom severity following baseline assessment and explored the time-varying relationship between perceptual and non-perceptual positive symptoms across adolescent development. Results: Perceptual positive symptom severity significantly decreased with increasing age ( F = 7.0, p = 0.0007; q = 0.003) while non-perceptual positive symptom severity increased with age ( F = 4.1, p = 0.01, q = 0.02). Anhedonia severity increased with increasing age ( F = 6.7, p = 0.00035; q = 0.0003), while flat affect decreased in severity with increased age ( F = 9.8, p = 0.002; q = 0.006). Findings remained significant when parental SES, IQ, and illness duration were included as covariates. There were no developmental effects on change in positive or negative symptom severity (all p > 0.25). Beginning at age 18, there was a statistically significant association between severity of non-perceptual and perceptual symptoms. This relationship increased in strength throughout adulthood. Conclusions: These findings suggest that as maturation proceeds, perceptual symptoms attenuate while non-perceptual symptoms are enhanced. Findings underscore how pathological brain–behavior relationships vary as a function of development.